2014
DOI: 10.3109/09513590.2013.876000
|View full text |Cite
|
Sign up to set email alerts
|

X-autosome translocations in amenorrhoea: a report of a three way translocation from Indian Population

Abstract: Chromosomal translocations have been reported in a number of women undergoing cytogenetic studies for amenorrhoea and gonadal dysgenesis. This study was taken up to emphasize the role of X chromosome and to know the frequency of X-autosomal translocations in women with amenorrhoea in Indian population. Cytogenetic analysis was carried out in 1567 subjects referred for amenorrhoea during the period 2002-2012. GTG-banding was performed from peripheral blood lymphocyte cultures to detect the chromosome abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Studies have revealed that patients with primary amenorrhea have male chromosome components [karyotype, 46, XY] but feminine phenotypes (Swyer syndrome) such chromosomal abnormalities are related with sex transformation, also some time the anomalies are related to X chromosomes, several forms of primary amenorrhea such as 47/XXX and 45/XO [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that patients with primary amenorrhea have male chromosome components [karyotype, 46, XY] but feminine phenotypes (Swyer syndrome) such chromosomal abnormalities are related with sex transformation, also some time the anomalies are related to X chromosomes, several forms of primary amenorrhea such as 47/XXX and 45/XO [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Female patients with this abnormality may present late in life with amenorrhea or delayed puberty. Early presentation was also reported in males and females with variable syndromes, including multiple congenital anomalies, mental retardation, or failure to thrive according to the breakpoints in the X chromosome and the autosome [Sugio et al, 1998;Tzschach et al, 2006;Shetty et al, 2014].…”
mentioning
confidence: 99%